PELAKSANAAN PROJEK STEM DALAM PROSES PENGAJARAN DAN PEMBELAJARAN SAINS DAN MATEMATIK KANAK-KANAK PRASEKOLAH DI ACEH TENGAH - Hasnawati Hasnawati (JIP: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study was to identify the implementation of STEM Project in the teaching proses of science and mathematics for preschool children in Cental Aceh. This study also found out the differences STEM projects implementation based on demographic factors. There were 175 respondents randomly randomly selected from three regions in Central Aceh. This study used quantitative opproach with two types analysis descriptive and inferential. The questionnaire consisted of 74 items and distributed to kindergartens. The conceptual framework was been built based on Vandel Logic Model et al., (2014), which consisted of eight domains of STEM Project (general, human, science, animal science, environment poll, numerical, numbers, geometric, and quantum mathematical. The findings of the questionnaire descriptive analysis ashowed that the overall domain of the STEM project had a mean mean score of general domain (m = 304) followed by quantity mathematics (m = 2.95), mathematics number (m = 2.89), animal science (m = 2.85 ), geometric mathematics (m = 2.85), environmental science (m = 2.81), science (m = 2.81), and human sciences (m = 2.71) where respondents are unsure about implementing STEM project in the kindergarten. Thuse for the inferesial analisis t – test determined that there the findings show that there was no significant difference in the comparison of the STEM project implementation differences except for the implementation of STEM projects based on age, education level and respondents' income. Lastly, the researcher suggested that in the science mathematics could develop children multiple intelegences.